Penerapan akidah tauhid dalam kepimpinan pendidikan - Mohamad, Ahmad Marzuki (2014)
This study aims to identify the principles of tauhid in the leadership practices of the principals of SMKA, (Malaysian National Religious School). This qualitative study uses interviews and observation as data collection instrument. Chosen by cluster sampling, respondents in this study were eight principals that represented the schools in western and northern zones of Peninsular Malaysia. The findings showed that these SMKA principals successfully inculcate the principles of tauhid in their leadership through various school activities involving the whole school community. It was also found that the school environment that was created through the teachings of Islam as a way of life has been able to improve the school pupils’ self-esteem and leadership.